Alat Pengontrolan Suhu Ruangan Serta Pemberian Pakan dan Air pada Produk NPD Kandang Ayam Menggunakan Arduino di Tanjung Uban - Zulfachmi Zulfachmi; Atanasius Nong (Prosiding, 2022)
Room temperature controller and chicken feeding using arduino designed to make it easier for farmers to control room and automatic feeding system. This research aims to maintain and control the temperature of the chicken coop which is a special obstacle for herders with an unstable and uncertain climate. This research uses devices such as Arduino Uno R3 Microcontroller, RTC, 4 Channel Relay, Water Level, DHT11, Van Theo, Servo, LCD. CM Sensor DHT 11 is used as a temperature gauge for the enclosure, this sensor will work to turn fan if temperature >32° and <24° then light will turn on. Feeding system moves automatically using servo motor as main driver in opening the feed tandon lid, the water level sensor serves as data input to arduino to instruct the relay to connect selenoide valve, as the main driver to open water access from the water toren. This room temperature control tool and feeding and water can help farmers to be able to do other activities to support family economy. This tool system uses low power electric current so it is very economical for chicken farmers.